Biomimetic implants for pelvic floor repair. Issue 2 (11th August 2017) - Vashaghian, Mahshid; Zaat, Sebastianus J.; Smit, Theodoor H.; Roovers, Jan‐Paul
Abstract : Background: Polypropylene implants are used for the reconstructive surgery of urogynaecological disorders like pelvic organ prolapse, but severe complications associated with their use have been reported. There is evidence that surface properties and a difference in mechanical stiffness between the implant and the host tissue contribute to these adverse events. Electrospinning is an innovative engineering alternative that provides a biomimetic microstructure for implants, resulting in a different mechano‐biological performance. Aim: The main objective of this review is to inform about the potential of electrospun matrices as an alternative modality for pelvic floor repair. Methods: Publications with the following studies of electrospun matrices were reviewed: (i) the technique; (ii) in vitro use for soft tissue engineering; (iii) in vivo use for reconstruction of soft tissues in animals; and (iv) clinical use in humans. Results: Electrospun matrices provide a synthetic mimic of natural extracellular matrix (ECM), favoring cellular attachment, proliferation and matrix deposition, through which a proper, low‐inflammatory tissue‐implant interaction can be established. Electrospun sheets can also be created with sufficient mechanical strength and stiffness for usage in prolapse surgery. Conclusion: Electrospun matrices mimic the structural topography of the extracellular matrix and can be functionalized for better biological performance. As such, they have great potential for the next generation of urogynecological implants. However, their long‐term safety and efficacy must still be established in vivo.